Analogical model tests on repeated surficial failure of dry granular slopes confined by retaining walls - Yang, Hufeng; Xing, Bencong; Jiang, Hu; Cheng, Qiangong (Frontiers in Earth Science, 2022)
In alpine and gorge regions, surficial failure of granular slopes has seriously affected the construction of infrastructure and the safe operation of transportation networks. This research focuses on dry granular slopes confined by the retaining wall. The repeatedly surficial failure of granular slopes has been explored through indoor physical model tests. The results show that the feature of surficial failure presents a low frequency but a large scale for the granular slope dominated by coarse particles. The mass of debris across the retaining wall indicates the activity level of granular slopes. When the mass of debris for each surficial failure event gradually decreases, it is highly likely that large-scale surficial failure will occur. As the amount of debris deposited on the slope increases, it is highly likely that the mass of debris falling during a massive sliding event will be many times that of the previous sliding event. In engineering practice, it is necessary to record the volume of debris accumulated on the road during road cleaning processes along with the dates. The continuous increase in the slope angle indicates a high probability of large-scale surficial failure. For each granular slope with a unique particle composition, there is a critical change rate for early warning on surficial failure, which can be obtained by long-term monitoring.